PERSEPSI PELAJAR UNIVERSITI TEKNOLOGI MALAYSIA (UTM) TERHADAP PLAGIARISME (Sains Humanika, 2008)
Plagiarism is one of the crimes committed in tertiary education institutions and it destroys the academic integrity among academicians. Plagiarism will hinder the materialization of the academic community objective in developing the students’ intellectuality and ethics. Thus, this study is important to survey the university students’ perception regarding the plagiarism practice. This study examined the UTM students’ perception on plagiarism. The objective of this study is to ascertain the tendency of plagiarism among the students and to know their views regarding the plagiarism practice. This study is a survey research quantitative data. 710 respondents UTM Skudai students who registered in ULT 3042 in the first semester of 2003/04 session have been selected as the research sample. A set of questionnaire based on the McCabe Academic Integrity Survey (M–AIS) had been distributed and 341 sets were returned. The result of this study is that the frequency of the plagiarism committed by the UTM students is low and there is a variety of perceptions on the nine behaviors proposed.
Keywords: Plagiarism; integrity; moral right; academic dishonesty; understanding